AUDITING THE VALUATION OF DERIVATIVE CONTRACTS: RECOGNITION, EVIDENCE, AND CONTROL ISSUES - Chant, Peter D. (Assurances, 1999)
This paper considers three issues that confront the auditor of derivatives. These issues are: 1. Recognition, meaning the identification of the circumstances in which derivatives occur, and must therefore be valued; 2. Appropriate audit evidence, meaning the determination of appropriate evidence when estimates of values must be audited; and 3. Procedures for gathering that evidence in a systematic fashion, given that auditors try to avoid replication-intensive activity. This paper will not consider the strategic uses or abuses of derivatives, or the evaluation of complex strategies, or performance measures. Nor will it deal with the accounting issues that surround derivatives, such as the categorization of certain contingent claims as being "remote" or "trivial", or the determination of an option as being "reasonably assured" or even "virtually assured" of being exercised. These are purely accounting policy matters, not related to valuation.